Crisis of faith or faith of crisis - Bezniuk, Dmitry K. (Journal of the Belarusian State University. Sociology, 2020)
Some indicators of the religiosity of the population of Belarus according to the results of opinion polls 2017–2019 are presented. Global characteristics are distinguished against which the religious situation is developing, and a system of factors characterizing the specificity of religiosity in modern Belarus. An attempt is made to forecast a change in religiosity.